К вопросу об аквариуме. Расширение границ водного мира в городской среде - Grigorieva, Anna (проект байкал, 2016)
In April 2016, arch out loud announced the winners of the international architectural competition, the task of which was to design NYC AQUARIUM & PUBLIC WATERFRONT. The first place was occupied by NYC AQUATRIUM designed by Italian architects.